Meningkatkan Kreativitas Siswa Pada Mata Pelajaran Seni Budaya Dengan Memanfaatkan Barang Bekas - Imroati, Imroati (Universitas Hamzanwadi, 2019)
This study aims to describe the extent to which students improve their creativity in the eyes of the arts and culture by utilizing second-hand items in class VIII 3 of SMP Negeri 1 Pringgasela. This study uses a classroom action research. This research was conducted in SMP Negeri 1 Pringgasela in August to September 2017 in 4 meetings with 2 cycles. The results of this study indicate that on the first cycle there is an increase based on the average percentage of students 'creativity in making artworks by utilizing second hand items at 35.19%, this means that students' creativity is still relatively low, so it is resumed in cycle II, for improvement. With the results of observations and assessments of students' creativity in making artworks by utilizing used items above, it can be explained that in each component there has been a significant increase, the percentage of creativity is mostly above 50%. The average percentage for all components is 63.89% and is in the medium category, while the increase in students' creativity in making artworks by utilizing second-hand items at each cycle is above 25% with an average increase for all compones of 28.70 %.